Tunnel diode oscillator technique for penetration depth studies of superconductors - Tam, Qian Xin (2013)
Tunnel diode oscillator (TDO) is a powerful technique for measuring the penetration depth of superconductor down to 10 mK-scale temperature. This final year project is part of the long term program to set up a TDO in our lab. The aims here are to solve two of the main difficulties in TDO, namely the home-making of low-temperature electronics and the detection of weak signal (~ 0.1 uV, ~ 20 MHz) by room-temperature electronics. I had designed and fabricated a "Nitrogen Probe" which is essentially a low temperature exchange gas chamber that enables me to prototype the low-temperature electronics at 77 K. In the experiment, the intended signal is highly degraded by parasitic oscillation from the low-temperature electronics and stray radio frequency (RF) noise from the surrounding. The parasitic oscillation was minimized through changing the components of the low-temperature electronics on a trial-and-error basis. RF shielding technique in particular the use of semi-rigid coax was found to be effective in removing the surrounding RF noise. I managed to set up a low-temperature electronics that makes oscillation at 77 K. However, the oscillation frequency is not stable which in turn affects the precision of the TDO. Hence, future work will be focusing on obtaining a high stability oscillation.